Comparative study of Bangladesh Barapukuria coal with those of various other countries - Safiullah, S; Khan, MRR; Sabur, MA (Journal of the Bangladesh Chemical Society, 2012)
Comparative study of the qualities of the Bangladeshi, Indian, Australian and Indonesian coals was made in terms of coking properties, calorific value, sulfur content, moisture, ash, volatile matters and carbon content. Bangladesh Barapukuria coal was found to be the best of all the coal samples with a carbon content of 56.47% and other qualities Bangladeshi coal clearly indicate that it is also suitable for value added utilization. DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9712 Journal of Bangladesh Chemical Society, Vol. 24(2), 221-225, 2011